"Exceeding Beringia": Upending universal human events and wayward transits in Arctic spaces. (February 2021) - Smith, Jen Rose
In this article I examine the enlistment of Arctic ice to tell grand, universal stories about humanity's origins and endings. Specifically, I analyze 18th century Natural History musings that linked Arctic climate to race and human difference. I demonstrate that these musings are constitutive to an invention of pathologized migrancy across Arctic spaces that emerge as a consequence of the inability of ice to foster agricultural settlement. I call this phenomenon temperate-normativity, in which Arctic spaces of ice are produced as inferior, not meaningful on their own but read as where transit to temperate locales occurs and those who linger are consequentially rendered as aberrant. To upend temperate-normative ideals of landscape and livelihood, I analyze a poem titled "Exceeding Beringia" by Joan Naviyuk Kane (Inupiaq) wherein Inupiaq relations to more-than-human kin articulate transit and migration as a mutual, obligatory responsibility.